Pembuatan Standard Operational Procedure (SOP) Layanan Sirkulasi di Perpustakaan SMA Pertiwi 1 Padang - Okti Arizen Putra; Elva Rahmah (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
This paper discusses about construction of Standard Operational Procedure (SOP) of Circulation Service at SMA Pertiwi 1 Padang’s library. This paper aims to describe the preparation and construction of Operational Procedure (SOP) of Circulation Service at SMA Pertiwi 1 Padang’s library. The researcher used description method. Then, the technique of data collection is observation and interview.Based on the research it can be concluded that Firs’t, the preparation to construct the Standard Operational Procedure (SOP) of Circulation Service at SMA Pertiwi 1 Padang’s library includes (1) finding out needs; (2) evaluating and assessing needs; (3) determining needs;(4) determining alternative step. Second, the construction of Standard Operational Procedure (SOP) of Circulation Service at SMA Pertiwi 1 Padang’s library includes (1) collecting information bydiscussing and doing interview with the headmaster of staff of the library; (2) making the basic draft, trying out the instrument and asking approval to the headmaster of the library, trying out the existing instrument with SOP’s draft that has been discussed; (3) making and attaching SOP’s document proponent; (4) attaching the designer of SOP and the validator and; (5) attaching the constructional date, revision and the validation.Keyword: library, Standard Operational Procedure (SOP), services.